Perceraian dalam Keluarga Muslim di Jawa Barat - Ramdani Wahyu Sururie; Harry Yuniardi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2018)
This study aims to describe the causes of high divorce rates in Muslim families in West Java based on the decisions of the Religious Courts, and this study also aims to formulate a strategy to prevent the increase in divorce rates. This study uses descriptive analysis method with interview techniques, study documents on the decisions of the Religious Courts and literature studies. The results of this study indicate that the highest cause of divorce in the mulism family in West Java is due to economic factors, there is no harmony and no responsibility. Prevention strategies for increasing divorce rates in West Java need to be done systemically from top to bottom, starting from family education before marriage and during conflicts between husband and wife. Thus, it can be concluded that the cause of the high divorce rate in Muslim families in West Java is due to a lack of commitment and knowledge of the essence of marriage, which makes the marital bond in a Muslim family fragile. The strategy to prevent increasing divorce rates is done systemically involving various elements, namely the government, community institutions, and the Religious Courts.